EXTH-81. STING ACTIVATION PROMOTES ROBUST IMMUNE RESPONSE AND TUMOR REGRESSION IN GLIOBLASTOMA MODELS. (12th November 2021) - Berger, Gilles; Knelson, Erik; Nowicki, Michal; Mooney, David; Chiocca, E Antonio; Barbie, David; Lawler, Sean
Abstract: The immunosuppressive tumor microenvironment in glioblastoma presents a major barrier to effective application of immunotherapeutic approaches in this disease. Although immunotherapy has had a tremendous impact on cancer treatment in the past decade, with hitherto unseen responses at advanced and metastatic stages of the disease glioblastoma remains largely refractory to current immunotherapeutic approaches. The cGAS-STING cytoplasmic double stranded DNA sensing pathway has emerged as a next-generation immunotherapy target with potent local immune stimulatory properties, but has not been well investigated in glioblastoma to date. Here we investigated the presence of STING pathway components in glioblastoma patient specimens and cell lines by Western blotting and immunostaining. The functionality of the pathway was determined by ELISA, and immune infiltrates, and animal survival were investigated in mouse glioblastoma models after treatment with the STING agonist ADU-S100. Our data reveal the presence of STING in human GBM specimens, where it stains strongly in the tumor vasculature, and appears to be activated as evidenced by elevated phosphoTBK1 staining. We show that human GBM cells do not respond agonists, but that GBM explants can respond to STING agonist treatment by secretion of inflammatory cytokines. In murine GBM models, we show a profound shift in the tumor immune landscape after STING agonist treatment, with massive infiltration of the tumor-bearing hemisphere with innate immune cells including inflammatory macrophages, neutrophils and NK populations. Treatment of established murine intracranial GL261 and CT-2A tumors by biodegradable ADU-S100-loaded intracranial implants demonstrated a significant increase in survival in both models and long-term survival with immune memory in GL261. This study reveals therapeutic potential and deep remodeling of the TME by STING activation in GBM and warrants the further examination of STING agonists alone or in combination with other immunotherapies such as cancer vaccines, CAR T cells, or immune checkpoint blockade.